Unfolding Layers of Meanings: Visual-Verbal Relations in Just Ask—A Children’s Picture Book - Damayanti, Ika Lestari; Moeharam, Nicke Yunita; Asyifa, Firly (Universitas Pendidikan Indonesia, 2021)
Studies in the field of semiotics and children’s literature have described the relationship between the verbal and visual texts in picture books as both complex and subtle. These relationships are named differently across theories, yet they still note two possibilities, whether they support or are against each other in conveying meanings to the readers. This study seeks to explore the relations between visual-verbal modes depicted in a children’s picture book entitled Just Ask (author/illustrator by Sotomayor Lopez, 2019), viewed from the perspective of multimodality as proposed by Unsworth (2006). The analysis between the visual and verbal modes in the picture book is focused on ideational concurrence and ideational complementarity. The results indicate that meanings in Just Ask are negotiated through verbal and visual texts which may be complementary or have divergent relationships to one another. It is through such strategy that the suggested theme of the picture book, in this case accepting diversity, is consistently conveyed to the targeted readers. Since picture books are used vastly in EFL/ESL classrooms to enhance students’ reading experiences, this study may help teachers develop students’ ability to make meaning from verbal and visual texts and inspire their visual thinking strategies.